Buerger's disease. (August 2017) - Megson, Matthew; Collins, Michael; Hobbs, Simon
Abstract : Introduction: This case demonstrates some of the features associated with Buerger's disease. This is a disease affecting the distal arteries causing ischaemia to the limb. It is associated with young patients who are heavy smokers. Case description: A 27-year-old gentleman, who smokes heavily was admitted with ulcerated and necrotic toes. An angiogram was done which showed the cockscrew appearance of the more distal arteries classical of thromboanglitis obliterans, this is what causes the ischaemia. He was treated with smoking cessation and a standard five day course of Inoprost with good symptom relief. Results and conclusions: Though Inoprost has good symptomatic relief the disease will continue to progress until the patient has completely stopped smoking as the autoimmune reaction is triggered by a component within the cigarette. If these patients do not stop smoking they are likely to require an amputation of the limb. Take-home message: These patients require smoking cessation assistance. If these patients do continue to smoke, they often require amputation, therefore early counselling with an amputation service/physiotherapists is useful.